2015
DOI: 10.1017/s1368980015000518
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of breast-feeding for longer than 6 months on early pubertal development among children aged 7–9 years in Korea

Abstract: Objective: The present study was performed to investigate whether breast-feeding is associated with early pubertal development among children 7-9 years old in Korea. Design: Children were divided into those who did and did not receive breastfeeding for 6 months or longer in accordance with the recommendations of the WHO. Pubertal status was determined by clinical examination using Tanner staging. Setting: Prospective observational study. Subjects: We conducted a follow-up study of children aged 7-9 years in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
(38 reference statements)
3
18
0
Order By: Relevance
“…By 2016, the follow-up of children aged 9 years had been completed. The methodology of the cohort study has been reported elsewhere [ 20 , 21 ]. In this study, two SNPs were genotyped in the subjects who were followed up at least once.…”
Section: Methodsmentioning
confidence: 99%
“…By 2016, the follow-up of children aged 9 years had been completed. The methodology of the cohort study has been reported elsewhere [ 20 , 21 ]. In this study, two SNPs were genotyped in the subjects who were followed up at least once.…”
Section: Methodsmentioning
confidence: 99%
“…About 30% of all possible subjects agreed to participate in the study [ 16 ]. A detailed description of the cohort composition, including methodology, has been published elsewhere [ 17 ]. Through follow-up at 7 or 9 years of age, a diet-related questionnaire survey was performed using a food frequency questionnaire (FFQ) and questions related to dietary habits.…”
Section: Methodsmentioning
confidence: 99%
“…Although the study estimates were adjusted for potential confounding by maternal and family characteristics, the interpretability of the results is limited because adjustment also included body mass index (BMI) in childhood, a variable that could be a mediator in the causal pathway. In a study of 219 Korean children, after adjusting for age and sex, those who were breastfed for ≥6 months had lower odds of reaching a Tanner stage ≥2 at 9 years of age compared with children who were breastfed for <6 months (58). In a prospective investigation of 994 Filipino girls, every month of exclusive breastfeeding was associated with a 6% lower probability of menarche over the followup period after adjusting for socioeconomic, maternal, and birth characteristics (3).…”
Section: Infant Feedingmentioning
confidence: 99%
“…Second, many of the studies had large losses to follow-up, which could result in selection bias if both infant feeding practices and pubertal stage affected retention. Third, most studies were restricted to girls, which hinders the generalizability of findings; in addition, some of the investigations that included both girls and boys did not present results stratified by sex (58). Fourth, observational studies are subject to residual confounding, and some of the analyses (48) may have incurred overadjustment bias.…”
Section: Infant Feedingmentioning
confidence: 99%